Coronavirus: impact on the sports industry worldwide (Statista, 2020)
Statista dossier on the effect of the coronavirus disease (COVID-19) on sports This dossier provides some of the most recent data relating to the impact of the ongoing coronavirus disease (COVID-19) pandemic on the global sports industry. The pandemic, which originated in the Chinese city of Wuhan, has now infected people across the globe. This dramatic spread has led to sports events across the globe being canceled and many professional leagues being suspended or postponed. This has had a significant impact on not only the fans of these sports, but also those working in the industry and even the economies of entire nations. This dossier provides insight into the potential economic impact of the coronavirus on various sports and events, as well as public opinion on the virus' impact on sport. Table of contents